Performance and microbial community analysis of a bio-contact oxidation reactor during the treatment of low-COD and high-salinity oilfield produced water. (September 2021) - Zhou, Hanghai; Chen, Chunlei; Zhou, Shaoxiong; Bu, Kuiyong; Li, Pingyuan; Lin, Xiaoyun; Jiang, Lijia; Zhang, Chunfang
Graphical abstract: Highlights: The BCOR can effectively remove pollutants from the oilfield produced water. The first BCOR stage played a major role in pollutants removal. The functional genera in pollutants removal were disclosed by correlation analysis. Non-random co-occurrence and function-driven modular patterns were exhibited. Abstract: The multistage bio-contact oxidation reactor (BCOR) is a widely used biological strategy to treat wastewater, however, little is known about the performance and microbial community information of BCOR during the treatment of low-COD and high-salinity oilfield produced water. In this study, the performance of a multistage BCOR in treating produced water was investigated. The result suggested the BCOR could efficiently remove COD, BOD5, NH4 + -N, and oil pollutants. Besides, high-throughput sequencing analysis revealed that oil content was the main variable in shaping the community structure. The highest total relative abundance of potential pollutants degraders in first BCOR stage suggested significant role of this stage in pollutants removal. In addition, the correlation analysis disclosed the key functional genera during the degradation process, including Rhodobacter, Citreibacter, and Roseovarius . Moreover, network analysis revealed that the microbial taxa within same module had strong ecological linkages and specific functions.